เปรียบเทียบผลเฉลยของปัญหาสติค-สลิป โดยวิธีทำซ้ำจาโคบี และวิธีทำซ้ำเกาส์-ไซเดล - ทองจับ นวลักษณ์ (RMUTP Research Journal Sciences and Technology, 2014)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อเปรียบเทียบการคำนวณหาผลเฉลยของวิธีเชิงตัวเลข 2 วิธี คือ วิธีทำซ้ำจาโคบีและวิธีทำซ้ำเกาส์-ไซเดลของปัญหาสติค-สลิปที่ท่อดายของกระบวนการอัดรีด โดยใช้วิธีสมาชิกจำกัดแบบ เซมิอิมพลิซิทเทย์เลอร์-กาเลอร์คินเพรซเชอร์คอร์เรคชัน ในการพิจารณาสมการเนเวียร์-สโตกส์ เพื่อประมาณค่าความเร็วและความดัน สำหรับของไหลนิวโตเนียนในระบบพิกัดทรงกระบอก 2 มิติ และปรบปรุง ผลเฉลยให้แม่นยำโดยใช้เทคนิคเกรเดียนท์รีคัฟเวอรี การวิเคราะห์ลู่เข้าแสดงว่าวิธีทำซ้ำเกาส์-ไซเดลลู่เข้าสู่ผลเฉลยจริงดีกว่าวิธีทำซ้ำจาโคบี เนื่องจากผลเฉลยจากวิธีทำซ้ำเกาส์-ไซเดลมีจำนวนทำซ้ำน้อยกว่าวิธีทำซ้ำจาโคบี Abstract This object of research is to compare the computation solution of two numerical methods. The methods were Jacobi iteration method and Guass-Seidel iteration method for the stick- slip problem at die of the extrusion process. The Navier-Stokes equation was analysed by finite element method of semi implicit Taylor-Galerkin/pressure-correction scheme to approximate velocity and pressure for Newtonian fluid in two dimentional cylindrical coordinate system. Solution accuracy was improved by the gradient recovery technique. The convergence analysis revealed that Guass-Seidel method approach to exact solution was better than Jacobi iteration method, that is because Guass-Seidel iteration method had less solution than Jacobi iteration method.